Idiopathic Ventral Spinal Cord Hernia—A Single-Center Case Series of 11 Patients. Issue 3 (28th March 2023) - Jesse, Christopher Marvin; Gallus, Marco; Beck, Jürgen; Ulrich, Christian T.; Seidel, Kathleen; Piechowiak, Eike; Dobrocky, Tomas; Häni, Levin; Schär, Ralph T.; Raabe, Andreas
Abstract : BACKGROUND: Idiopathic spinal cord herniations (ISCH) are rare defects of the ventromedial or mediolateral dura mater with herniation of the spinal cord through the defect with approximately 350 described cases worldwide. Patients usually become symptomatic with motor or sensory neurological deficits and gait disturbances. OBJECTIVE: To describe characteristic symptoms and clinical findings and to evaluate the postoperative course and outcomes of ISCH. METHODS: We present a single-center data analysis of a case series of 11 consecutive patients who were diagnosed with ISCH and underwent surgery in our department between 2009 and 2021. RESULTS: All herniations were located in the thoracic spine between T2 and T9. In most cases, gait ataxia and dysesthesia led to further workup and subsequently to the diagnosis of ISCH. A "far-enough" posterior-lateral surgical approach, hemilaminectomy or laminectomy with a transdural approach, was performed under intraoperative neurophysiological monitoring which was followed by adhesiolysis, repositioning of the spinal cord and sealing using a dura patch. After surgery, clinical symptoms improved in 9 of 11 patients (81.8%), while only 1 patient experienced deterioration of symptoms (9.1%) and 1 patient remained equal (9.1%). The median preoperative McCormick grade was 3 (±0.70), while the median postoperative grade was 2 (±0.98) ( P = .0047). CONCLUSION: In our case series of ISCH, we found that in most patients, neurological deficits improved postoperatively. This indicates that surgery in ISCH should not be delayed in symptomatic patients.